2016
DOI: 10.1016/j.ijsu.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and risk factors of hypoparathyroidism after total thyroidectomy

Abstract: Female gender (P = 0.001), extent of CND (P = 0.014), and PTG in permanent pathologic sections (P = 0.035) were found to be significant factors affecting the development of hypocalcemia. Despite some study limitations, we suggest that the relative changes in the serum levels of calcium (20%) and of phosphorus (40%) on the second postoperative day may be reliable predictors of post-thyroidectomy hypoparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 23 publications
3
53
2
6
Order By: Relevance
“…As expected, these patients have low serum PTH level in the postoperative period. Lymph node dissection and malignancy have been reported as risk factors for developing HPP [13]. It has been reported by various studies that central lymph node dissection impairs blood supply of the parathyroid glands or inadvertently causes the performance of parathyroidectomy or autotransplantation during surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, these patients have low serum PTH level in the postoperative period. Lymph node dissection and malignancy have been reported as risk factors for developing HPP [13]. It has been reported by various studies that central lymph node dissection impairs blood supply of the parathyroid glands or inadvertently causes the performance of parathyroidectomy or autotransplantation during surgery [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, those who undergo peripheral ligation of the inferior thyroid artery at the thyroid capsule are more prone to develop hypoparathyroidism than those who undergo subcapsular dissection (10). Parathyroid auto-transplantation, inadvertent excision of PGs and presence of PGs in the thyroid specimen have also been shown to increase the risk of post-operative hypoparathyroidism (1,(11)(12)(13)(14)(15)(16)(17). This is because they all lower the number of in situ PGs and therefore, the residual parathyroid function is immediately compromised.…”
Section: Risk Factors Leading To Postoperative Hypoparathyroidismmentioning
confidence: 99%
“…Some suggested that an early postoperative decrease in serum iPTH concentrations (8,10), combining with serum Ca concentration may predict hypoparathyroidism and guide the administration of Ca or vitamin D supplements (18,19). Post-operative hypoparathyroidism results from a reduction of functioning parathyroid parenchyma, which could be secondary to intraoperative damages caused by mechanical or thermal trauma, gland devascularization, obstruction of venous outflow, and inadvertent parathyroid excision (14,15,17). Therefore, the question has been whether there are strategies or approaches a surgeon could follow intra-operatively to minimize PG injuries and hypoparathyroidism.…”
Section: Risk Factors Leading To Postoperative Hypoparathyroidismmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies include phosphorus and magnesium as predictors of hypocalcemia; however, their predictive value is significant since the second postoperative day. (15)(16)(17).…”
mentioning
confidence: 99%